Experimental optimization of welding current, strip thickness, and spot number for the mechanical integrity of 18650 lithium-ion battery pack joints - Arman Arman; Widya Jufri; Baso Nasrullah (Politeknik Negeri Lhokseumawe, 2025)
The accelerating transition to renewable energy has driven widespread use of 18650 lithium-ion cells in electric vehicles and portable electronics, making the integrity of resistance spot-welded joints critical for system safety and reliability. This study investigates the effects of material thickness, number of weld points, and welding current on the mechanical performance of spot-welded joints. SPCC nickel strips with thicknesses of 0.10 mm, 0.12 mm, and 0.15 mm were welded to 18650 cells using a CNC-controlled spot-welding machine in three operating modes (7, 8, and 9). The mechanical performance was assessed through shear and peel force tests. The results showed that the welding current and the number of weld points had a dominant influence on the joint load-bearing capacity. Six weld points consistently improved load distribution, while material thickness significantly improved performance, with a 0.15 mm strip producing the highest shear force of 2380 N and a peel force of 2400 N. Optimal performance was achieved at 25 A (Mode 9), where failure occurred primarily in the base metal, indicating a strong metallurgical bond. SEM analysis shows the 0.12 mm thickness produces more homogeneous surfaces with fewer micro-cracks. The results reveal a trade-off between performance metrics, where 0.15 mm achieves higher load-bearing capacity, whereas 0.12 mm offers improved microstructural stability and long-term reliability. Optimizing spot welding parameters is essential for achieving reliable battery interconnections, as increasing the number of weld points enhances mechanical robustness while appropriate current levels improve joint integrity without inducing thermal damage.